Gender-related factors that influence uptake of HIV Services in women who inject drugs: a community based qualitative study in St Petersburg, Russia - Elizabeth J King, PhD; Olga Alexandrova, PhD; Julia Batluk, MA; Alla Shaboltas, PhD (Elsevier, 2020)
Background: People who inject drugs have been particularly affected by the HIV/AIDS epidemic in Russia. Women who inject drugs are highly susceptible to HIV infection, are often marginalised in service provision, and are in need of gender-tailored intervention strategies. However, there is a paucity of up-to-date, in-depth research on the specific needs of these women in the current political and social climate in Russia. The objective of our research was to identify and explore the gender-related factors that affect uptake of HIV services among women who inject drugs in Russia. Methods: Guided by the Theory of Gender and Power, we conducted a community-based qualitative research project in St Petersburg, Russia. We conducted in-depth interviews with 30 women who inject drugs and 20 service providers. Women who inject drugs were recruited through community outreach services using a purposive sampling strategy to ensure diversity in HIV status, age, marital status, and involvement in sex work. Service providers were from organisations involved in drug rehabilitation, HIV-related medicine, family services, and non-governmental services. We used thematic analysis to code our audio-recorded and transcribed data. Our analysis benefited from the interdisciplinary and international research team approach. Findings: Interviews took place between June 20 and Nov 5, 2018; the mean age of women was 36 years (range 23-44 years), 12 participants (40%) were unmarried, 15 (50%) had children, average duration of drug use was 16·5 years (range 3-30 years), 20 (67%) reported engagement in sex work, and 20 (67%) reported an HIV-positive status. Respondents, both women who inject drugs and service providers, reported reasons for not going to an HIV clinic for diagnosis and treatment that included: fear of being treated poorly because of their drug use; a lack of knowledge about treatment options; difficulty in acceptance of diagnosis; organisational factors such as timing, location, and wait times; and challenges motivating oneself to go. For some respondents, motherhood was a motivator for seeking care, whereas others avoided seeking care for fear of losing custody of their children. Another salient theme was women's codependence. For example, they prioritise seeking treatment for their male partner before presenting for care themselves. Factors that facilitated care-seeking were contact with peer educators, the support of family and partners, and connecting with supportive doctors. Interpretation: Women who inject drugs are in need of interventions that take into account issues of gender and the power dynamics within interpersonal relationships, family structures, interactions with providers in the medical care and social services systems, and at the community level. In the post-Global Fund era, Russia must develop interventions tailored to its population, including addressing the needs of women who inject drugs. Funding: University of Michigan Office of Research and University of Michigan Office of Global Public Health.